Japanese Foreign Policy Towards Latin America and the Caribbean: Between Cooperation and Business [la Política Exterior Japonesa Hacia América Latina y el Caribe: Entre la Cooperación y Los Negocios] - Ross-Orellana, C (2012)
Japanese foreign policy has typically been characterized by its most visible features, trade and cooperation, while lacking a political and ideological dimension. In the middle of the 90s this vision was qualified through the addition of another dimension (D. Arase) which affirmed that cooperation was concealing a well-planned diplomatic strategy to increase Japan s political influence at the international level, thus creating an alternative to what was known as the Yoshida doctrine. The application of David Arase s thesis to the specific case of Latin America and the Caribbean allows us to observe that, while theoretically credible, it lacks sufficient empirical support to be considered entirely true. In the following pages we present the uniqueness of the problem as well as counter-evidence to Arase s thesis.